Leech therapy and adjuvant Ayurveda treatment in the management of diabetic foot ulcer with atherosclerosis - Snehal R Sonani; Tukaram S Dudhamal (Wolters Kluwer Medknow Publications, 2023)
Diabetic patients are more prevalent to atherosclerosis (29.1%); however, its pathophysiology is still unclear. Such cases mostly convert into either amputation due to rapid spread or lifelong anticoagulant. Ayurveda is famed to be a tool in prevention and management of such fatal or disabling surgeries by parasurgical procedure, i.e., leech therapy, Agnikarma, etc. This study presents a case of postdiabetic atherosclerosis (male/54 years old) with a complaint of blackening of the great toe of the right lower limb and and other associated symptoms such as intermittent claudication (Garde 4), Burning in sole, occasional numbness in the foot. this case was managed by the Ayurveda para-surgical procedure (Leech therapy). The patient was a known case of DM and taking medication for it for the last 1 year, but his blood sugar level was found to be uncontrolled (HB1Ac: 9.90). The patient had surgical history of coronary artery bypass graft before 8 years. His bilateral lower limb computed tomography angiography was suggestive of diffuse atherosclerotic fibrocalcified wall plaques in abdominal aorta, iliac, femoral, and both leg arteries. Clinical examination revealed black right greater toe with line of demarcation and on palpation, feeble femoral artery and downstream non-palpable arteries. As a part of treatment, leech application along with some rejuvenating oral drugs i.e. Sanjvani vati and pippali churna was given to the patient. On 2nd week of treatment protocol, black gangrenous great- toe was amputed which afterwards become open wound(approx.2cm x 2 cm). Afterward, daily wound dressing was done with Apamarga kshar taila or Thumari taila (As per the status of the wound) after cleaning with Triphala Kwath. After completion of treatment protocol, the patient got 85-90% relief in clinical symptoms and also previously feeble arteries were felt with full volume.